2009
DOI: 10.1111/j.1600-0501.2009.01870.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the socket bone wall dimensions in the upper maxilla in relation to immediate implant placement

Abstract: If the criterion of a minimal buccal bone width of 2 mm to maintain a stable buccal bony wall is valid, only a limited number of sites in the anterior maxilla display such a clinical situation. The data suggested that in the majority of extraction sites in the anterior maxilla, thin (< or = 1 mm) buccal walls were present. This, in turn, means that in most clinical situations encountered, augmentation procedures are needed to achieve adequate bony contours around the implant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
219
1
21

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 249 publications
(254 citation statements)
references
References 22 publications
13
219
1
21
Order By: Relevance
“…A study by Huynh--Ba et al [31] has shown that only a small portion of maxillary front teeth have a vestibular bone thickness greater than or equal to 2 mm (6.5%). As many as 78% of dental elements have a vestibular bone thickness less than 1 mm and 46% even less than or equal to 0.5 mm.…”
Section: Vertical and Horizontal Bone Resorption Following Immediate mentioning
confidence: 99%
“…A study by Huynh--Ba et al [31] has shown that only a small portion of maxillary front teeth have a vestibular bone thickness greater than or equal to 2 mm (6.5%). As many as 78% of dental elements have a vestibular bone thickness less than 1 mm and 46% even less than or equal to 0.5 mm.…”
Section: Vertical and Horizontal Bone Resorption Following Immediate mentioning
confidence: 99%
“…En effet, il est admis qu'un positionnement palatin de l'implant et la présence d'une corticale vestibulaire de 2 mm permettent une meilleure vascularisation garantissant la stabilité de l'implant et des tissus mous sus-jacents [15]. Cependant, une analyse récente montre que cette épaisseur n'est retrouvée que dans 3 % des cas dans le secteur antérieur et, dans 87 %, elle est même égale ou inférieure à 1 mm [16]. Il existe donc souvent un risque de résorption de la table externe que l'avulsion implantation immédiate n'efface pas.…”
Section: Discussionunclassified
“…Current trend in implant therapy is shifting from conventional implant therapy to immediate implant therapy. According to Huynh-Ba et al, 10 placement of immediate implant may preserve bone dimensions. Analysis of bone dimensions is a must before immediate implant placement to determine the need of bone augmentation and appropriate treatment planning.…”
Section: Discussionmentioning
confidence: 99%